2023
DOI: 10.3389/fmed.2023.1246690
|View full text |Cite
|
Sign up to set email alerts
|

From bench to bedside – current clinical and translational challenges in fibula free flap reconstruction

Helena Baecher,
Cosima C. Hoch,
Samuel Knoedler
et al.

Abstract: Fibula free flaps (FFF) represent a working horse for different reconstructive scenarios in facial surgery. While FFF were initially established for mandible reconstruction, advancements in planning for microsurgical techniques have paved the way toward a broader spectrum of indications, including maxillary defects. Essential factors to improve patient outcomes following FFF include minimal donor site morbidity, adequate bone length, and dual blood supply. Yet, persisting clinical and translational challenges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 157 publications
0
3
0
Order By: Relevance
“…The repetitive bending of the plates may also result in increased fatigue and less resistance to corrosion, increasing the risk of plate fracture. Additionally, inappropriate selection of plate size or improper placement can create stress concentrations and is a crucial risk factor 2 , 15-17 . According to the literature, it is reported that plate fractures occur in 2.9%-10.7% of cases, with most occurring within 2 years after surgery, and often within less than 6 months 2 .…”
Section: Computer-aided Design and Computer Assisted Manufacturing (C...mentioning
confidence: 99%
See 1 more Smart Citation
“…The repetitive bending of the plates may also result in increased fatigue and less resistance to corrosion, increasing the risk of plate fracture. Additionally, inappropriate selection of plate size or improper placement can create stress concentrations and is a crucial risk factor 2 , 15-17 . According to the literature, it is reported that plate fractures occur in 2.9%-10.7% of cases, with most occurring within 2 years after surgery, and often within less than 6 months 2 .…”
Section: Computer-aided Design and Computer Assisted Manufacturing (C...mentioning
confidence: 99%
“…Although there may be some variations in the parameters proposed, the literature generally agrees that CAD/CAM-guided reconstruction provides greater accuracy and precision compared to traditional methods 2 . The restoration of the proper shape and correct relationships between the mandibular and maxillary bones can result in adequate support for the soft tissues of the face, restoration of symmetry, and in cases of maxillary defects, support for the nasal pyramid and orbital content 15-17 . Furthermore, the restoration of normal occlusal relationships and the position of the mandibular condyles in the glenoid fossa is crucial.…”
Section: Improved Functional and Aesthetic Outcomesmentioning
confidence: 99%
“…Virtual surgical planning has been developed to optimize reconstructive outcomes. Preoperative 3D virtual modeling of skulls created using preoperative computed tomography (CT) scans allows the surgeon to model the titanium plate before surgery, simplifying the intraoperative steps and decreasing operative time [8][9][10][11][12]. This protocol was first described in 1993 by Rose et al [13] and it became a milestone in the history of mandibular reconstruction.…”
Section: Introductionmentioning
confidence: 99%